2007
DOI: 10.1007/bf02912884
|View full text |Cite
|
Sign up to set email alerts
|

Paired values of serum fructosamine and blood glucose for the screening of gestational diabetes mellitus: A retrospective study of 165 Saudi pregnant women

Abstract: This study reports the utilization of serum fructosamine and blood glucose for the screening of gestational diabetes mellitus (GDM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…A short-term marker of glycemia is needed in GDM because HbA1c measurements are not reliable as glucose and iron concentrations decrease while erythrocyte turnover increases [290,291]. Fructosamine is a preferred alternative because it can be obtained from a single random blood sample and does not require an OGTT [292]. However, fructosamine was insensitive for identifying GDM in early pregnancy [293] .…”
Section: Fructosaminementioning
confidence: 99%
“…A short-term marker of glycemia is needed in GDM because HbA1c measurements are not reliable as glucose and iron concentrations decrease while erythrocyte turnover increases [290,291]. Fructosamine is a preferred alternative because it can be obtained from a single random blood sample and does not require an OGTT [292]. However, fructosamine was insensitive for identifying GDM in early pregnancy [293] .…”
Section: Fructosaminementioning
confidence: 99%
“… 64 Other researchers have utilized the serum fructosamine and blood glucose for the screening of GDM. 36 , 37 Both these tests allow the health-care providers to establish whether the pregnant women, with associated risk facts, had developed diabetes before the pregnancy, which may have gone undiagnosed. If the HbA1c levels are not monitored closely to establish acceptable glycemic control, the higher levels of HbA1c may cause the long-axis cardiac dysfunction in the developing fetus.…”
Section: Hba1c Rangementioning
confidence: 99%
“…Although paired values of blood glucose and serum fructosamine were also reported for the screening of GDM, there were significant fluctuations during several antenatal visits. 36,37 Prognostic Potentials of HbA1c…”
Section: Diagnostic Potentials Of Hba1cmentioning
confidence: 99%
“…As in other clinical settings, mixed evidence has been reported on the utility of fructosamine in screening and monitoring of gestational diabetes mellitus. Khan et al measured FPG and serum fructosamine in 165 pregnant women, 71 and found that FPG and fructosamine could identify high-risk individuals to be screened with the OGTT avoiding unnecessary glucose challenges. At variance with these findings, Li et al measured fructosamine in 161 pregnant women, 72 and reported that this biomarker may be useful for identifying patients at higher risk of abnormal glucose tolerance, but could not be used to predict gestational diabetes mellitus in early pregnancy due to the poor correlations with the outcome of the OGTT.…”
Section: Clinical Studies About Glycated Albumin and Fructosaminementioning
confidence: 99%